MARRIAGE UNDER AGE AND THEIR EFFECT ON THE RATE OF DIVORCE IN ROKAN HILIR DISTRICT - Mardalena Hanifah (Fakultas Hukum, Universitas Diponegoro, 2021)
Article 1 of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, marriage is an outer and inner bond between a man and a woman as husband and wife to form an eternal and happy family based on the One Godhead. One. In general, no one wants their marriage to end in divorce, different environments make the marriage untenable. The problem is the factors that cause underage marriage. The research method is sociological juridical with descriptive research nature. This study deals with family law. Based on the results of the research conducted, the factors causing underage marriage are a moral factor because married by accident, economic factors because their parents had arranged an arranged marriage with the following percentages, 40% experienced underage marriages because they were not mentally and religiously prepared, 30% Divorce occurs because they do not have a permanent job, and another 30% are due to arranged marriages and forced marriages.